Health values in the textbook of the Algerian school - Khineche, souad; amamra, samira (Journal of Social Sciences and Humanities, 2024)
The aim of the study is the attempt to learn about health values in the textbook of the Algerian school and to know the role of educational content in the acquisition of values. The importance of this study is that the Algerian school is a social institution that works to achieve values, including health values. Its role in providing pupils with healthy values becomes healthy patterns and behaviors practiced in their daily lives which protect them and others from disease. It also manages to address problems whether they are scientific, mathematical, ethical, educational, social, and healthful. This creates harmony and a balanced conscience in reality and becoming an effective person in his\her society. The study concluded with a conclusion on the role of the textbook currently adopted in the Algerian schoo l)my book in arabic the first year of primaryeducation) and its health values to be acquired by the pupil, which are defined in a number of behaviors, whether at the physical, psychological, community or environmental level, to be reached by a conscious individual and a practitioner of public or social health.